DEMOKRASI VS LIBERALISASI - Suryani, Elvira (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2011)
A democracy is a political system and ideology in which the people or community are made found from western. Democracy is an encouraging development of political equality and under conditions of political freedom, it’s mind a government of the people, by the people, for the people, either directly or through representatives.Liberalism comes from the word free.The Freedom to say their opinion for every citizen. While Freedoom is not free. The words is famous in United State. Democracy need the freedoom for saying the opinion about politic, economic and ect.